Microseismic moment tensor based analysis of rock mass failure mechanism surrounding an underground powerhouse. Issue 1 (1st January 2021) - Sun, Yuepeng; Li, Biao; Dong, Linlu; Mao, Haoyu; Xu, Nuwen; Zhu, Zhongping; Liu, Jinfei
Abstract: The failure mechanism of surrounding rock is an important issue in the field of underground engineering. To quantitatively understand the failure process and failure mechanism of the surrounding rock mass in deep underground engineering, the underground powerhouse of the Houziyan hydropower station was selected as a case study. The study area was determined by analysing the spatiotemporal distribution of microseismic (MS) events and site investigations. After noise reduction, P-wave arrival time extraction and positioning of MS signals, the moment tensor inversion method was used to determine the failure mechanism and fracture direction of the surrounding rock mass. The results showed that (1) the failure processes and mechanism of the surrounding rock mass can be effectively analysed through MS monitoring with moment tensor analysis and (2) the failure type of the surrounding rock mass downstream of the main powerhouse was characterized by shear failure. The stress state in this region was a strike-slip stress state. (3) The failure type of the surrounding rock mass at the arch roof of the main transformer chamber was characterized by tensile failure. The tensile stress of the intermediate stress axis was obvious, and the tectonic stress presented a state of near uniaxial compression-biaxial tension.